A case of COVID‐19‐related necrotic nasal ulceration. Issue 2 (23rd February 2023) - Angelou, Dimitrios; Calder, Nicholas
Abstract: We are reporting a case of a COVID‐19‐related necrotic nasal ulcer. All other common etiologies were excluded after a full round of investigations. Even though COVID‐19 has been known to cause skin ulcers via different mechanisms, this is the first nasal ulcer to be reported in the current literature. Abstract : COVID‐19 has been found to cause a spectrum of skin lesions. COVID‐19‐related nasal cutaneous ulcers can be a diagnosis of exclusion in patients where no other pathologies have been identified.